Clusters of creativity : enduring lessons on innovation and entrepreneurship from Silicon Valley and Europe's Silicon Fen - Koepp, Rob (Chichester : Wiley, 2002)
Like the subject matter it covers, Clusters of Creativity is innovative and original. It breaks with popular interpretations of Silicon Valley and similar regions, which range from the hyperbolically laudatory to the contemptuously dismissive, and takes a critical, objective look at the lessons that these locations provide about innovation and entrepreneurship.
Clusters of Creativity; Contents; Acknowledgements; 1 Introduction: The Hidden Lessons of "Siliconia'; The Silicon Valleys of the World; Silicon Valley in Context; Breaking with Accepted Orthodoxy; Clusters and Enterprise; SILICON VALLEY; 2 Introduction; 3 From Semi- desert to Silicon Valley; 4 Valley Dynamism; 5 Valley Innovators; 6 Post-silicon Silicon Valley; EUROPE'S SILICON FEN; 7 Introduction; 8 The Phenomenon of Cambridge; 9 Cambridge Dynamics; 10 Phenomenally Innovative; 11 The Future of the Phenomenon; 12 Epilogue: A Silicon World?; Endnotes; Index.
Includes bibliographical references and index
Keywords: Entrepreneurship -- California -- Santa Clara Valley (Santa Clara County); Entrepreneurship -- England -- Cambridge Region; High technology industries -- California -- Santa Clara Valley (Santa Clara County); High technology industries -- England -- Cambridge Region; Microelectronics industry -- California -- Santa Clara Valley (Santa Clara County); Microelectronics industry -- England -- Cambridge Region